The Influence of Pricing and Digital Promotion Through Instagram on Tourists' Purchase Interest at the Haven Bali Seminyak Hotel - Suryananta, I Putu Bagus; Suastini, Ni Made; Pitanatri, Putu Diah Sastri (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This study examines the effect of pricing and digital promotion through Instagram on tourist purchasing interest at The Haven Bali Seminyak. Using a quantitative method with 100 respondents, this study applies validity, reliability, multiple linear regression analysis, F test, T test, and coefficient of determination analysis. Data were processed using SPSS. The results show that pricing and digital promotion have a significant effect simultaneously and partially on tourist purchasing interest. Both variables contribute 61% to purchasing interest. Multiple linear regression analysis shows a positive effect of 0.337 for price and 0.317 for promotion. The T test produces a significance value of 0.000 <0.05 for both variables. The F test proves the significant effect of both variables together on purchasing interest with a significance level of 0.000 <0.05.